Hydrothermal Synthesis of Vanadium Phosphorus Oxide Catalysts for Selective Oxidation of N-Butane to Maleic Anhydride - Ab Rahim, Mohd Hasbi (2006)
Vanadium phosphorus oxide (VPO) catalyst is commercially used in industry for the selective oxidation of n-butane to maleic anhydride. A number of new methods have been suggested by researchers worldwide in the preparation of precursor compound, VOHPO4·0.5H2O which is subsequently transformed under suitable reaction condition to give the better catalysts in terms of selectivity to maleic anhydride and the n-butane activity. In this study, VPO catalysts were synthesized using a new hydrothermal method. Roughly, this study can be divided into three sections based on three groups of VPO catalysts prepared. The first catalyst was prepared following the procedure in the literature. The second group of VPO catalyst were prepared by the modification of this procedure which focused on different reaction time in autoclave. Lastly, the effect of mechanochemical treatment on the hydrothermal prepared sample was studied. The results show that VPO catalysts were successfully prepared by hydrothermal method. The morphology, structure, oxidant’s nature and catalytic performance for butane oxidation to maleic anhydride over these catalysts strongly depended on the preparation procedure of the VOHPO4 0.5H2O precursor and also the transformation into the VPO catalyst. Increasing the length of reaction time in autoclave at 423 K does not affect the surface area and bulk morphology of the catalyst. However, amounts of O2 removed and desorbed from the lattice are directly proportional with reaction time in autoclave. Interestingly, there are trends of results were observed for the milled material. This mechanochemical treatment contributed to a higher surface area with high mobility and reactivity of the lattice oxygen. The pretreatment also induced the amount of V5+ phase of the catalyst. An appropriate amount of V5+ phase present in VPO catalyst is significantly increased the activity of these catalysts